COP1 drives renal cell carcinoma progression by targeting ACSL4 for ubiquitin-mediated degradation and inhibiting ferroptosis - Zheng, Yuxiao; Jiang, Lei; Qi, Feng; Peng, Bo (Frontiers in Oncology, 2025)
BackgroundRenal cell carcinoma (RCC) progression is closely linked to dysregulation of the ubiquitin-proteasome system, particularly aberrant ubiquitination processes governing protein degradation and cell cycle control. As a pivotal E3 ubiquitin ligase, COP1 mediates substrate-specific ubiquitination to regulate protein stability. However, its functional role in RCC remains poorly characterized. This study investigates how COP1 drives RCC malignancy and explores its underlying molecular mechanisms.MethodsWe analyzed the expression of COP1 in RCC cells and its relationship with patient overall survival (OS) in databases. The CCK-8 assay was used to detect the effect of COP1 on the proliferation of RCC cells, while the Transwell assay was used to assess the impact of COP1 on the migration and invasion of RCC cells. We employed mass spectrometry, co-immunoprecipitation, Western blot, and RT-qPCR to explore the target proteins that interact with COP1 and their interaction modes. After inducing with ferroptosis inducers, we measured the effect of COP1 on lipid ROS levels in RCC cells. Finally, we validated the role of COP1 in RCC using in vivo experiments.ResultsCOP1 was significantly correlated with poor patient prognosis. Functional studies demonstrated that COP1 overexpression markedly increased RCC cell proliferation by 65% (786-O) and 58% (ACHN) (p < 0.001) and enhanced migration/invasion (p < 0.01), while COP1 knockdown suppressed these malignant phenotypes by 40–50%. Mechanistically, COP1 directly bound ACSL4 and promoted its K48-linked ubiquitination, reducing ACSL4 protein stability by 70% (p < 0.001) and suppressing ferroptosis, as evidenced by decreased lipid ROS levels (p < 0.01) and reversal of ferroptosis inhibition by ferrostatin-1. In vivo, COP1 overexpression accelerated tumor growth in xenograft models, with a 2.5-fold increase in tumor volume compared to controls (p < 0.001), accompanied by reduced ACSL4 expression and elevated Ki67 proliferation index. These effects were further amplified by the ferroptosis inhibitor ferrostatin-1, underscoring COP1’s role in driving tumor progression through ferroptosis suppression.ConclusionOur study establishes COP1 as a critical driver of RCC progression by suppressing ferroptosis through ubiquitin-mediated degradation of ACSL4, thereby providing a novel theoretical foundation for targeted therapeutic strategies in RCC.